Life skills development through sport: a bibliometric and systematic literature review - Nur Alam Rahmatullah; Komarudin; Boyke Mulyana (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2026)
Research on life skills development through sport has shown significant growth as sport is increasingly viewed as a medium for character building, social skills, and psychosocial development. However, the literature in this field remains fragmented and reflects various conceptual and pedagogical approaches. This study aimed to map the development of the literature, identify research trends, and analyze the major themes in life skills development through sport. The study employed a mixed-methods design by integrating bibliometric analysis and a Systematic Literature Review (SLR). Data were obtained from the Scopus database covering publications from 2007–2025 using keywords related to life skills and sport. A total of 100 articles were analyzed bibliometrically using VOSviewer and Biblioshiny, while 10 selected articles were analyzed through SLR based on the PRISMA 2020 guidelines. The findings revealed that publications on life skills development through sport have increased significantly since the mid-2010s, with dominant contributions from United States and Canada. The major themes identified included positive youth development, coaching, and life skill transfer. The SLR findings indicated that life skills development is influenced by explicit pedagogical approaches, the quality of coach-athlete relationships, and structured sport program design. This study concludes that sport has substantial potential as a medium for life skills development when programs are intentionally designed and pedagogically oriented. The findings are expected to contribute to the development of theory, coaching practices, and character-based sport programs, as well as provide directions for future studies on cross-cultural validation and long-term life skill transfer effectiveness.